Evaluation of Hypocaloric Diet With Protein Supplementation in Middle-Aged Sarcopenic Obese Women: A Pilot Study - Rosa Sammarco; Maurizio Marra; Maria Luisa Di Guglielmo; Marianna Naccarato; Franco Contaldo; Eleonora Poggiogalle; Lorenzo Maria Donini; Fabrizio Pasanisi (Obesity Facts, 2017)
Objective: The aim of this study was to evaluate the efficacy of a nutritional program, which is characterized by a different modulation of proteins, in adult patients with sarcopenic obesity. Methods: We studied 18 obese women aged 41-74 years. Obesity was diagnosed as fat mass > 34.8% and sarcopenia was defined when lean body mass was Results: Weight significantly decreased in both groups. Women with high-protein diet preserved lean body mass compared to low-calorie diet and improved significantly muscle strength; SPPB score did not change in both groups. SF-36 test showed a significant change for general health after 4 months in group B. Conclusions: In our study, sarcopenic obese patients with high-protein diet showed an improvement in muscle strength. Furthermore, dietary protein enrichment may represent a protection from the risk of sarcopenia following a hypocaloric diet.